Features of the Organizational Construction of System of Management of Sanatorium-Resort Institution (Economic journal of Lesya Ukrainka Volyn National University, 2016)
In this scientific article basing on the system analysis and the logical and structural framework are generalized the peculiarities of the organizational construction of system of management of sanatorium-resort institution. In particular: on the basis of application of system analysis are considered areas of activity organized in the sanatorium-resort institution. Using the methods of management analysis we have summarized the essence of medical rehabilitation and service processes and procedures of management of sanatorium-resort institution. The use of logical generalization has allowed to establish features of the system of management of such institutions. Using the method of the logical and structural analysis are selected blocks of the control system of workers of sanatorium-resort institution. The work of an organizational management system of sanatoriumaresort institution is depicted through the application of the logical and structural approach.
Keywords: sanatorium-resort institution; control system; the organizational structure of the management system of sanatorium-resort institution